Mėsos pavadinimai žemaičių šnektose - Vitkauskas, Vytautas (Baltistica, 1978)
The names of meat in the Žemaičiai dialects The names of meat in the Žemaičiai dialects differ from those in literary language and in the Aukštaičiai dialects. 1. The Southern Žemaičiai (Laũkuva, Vainùtas, Žviñgiai, Žygáičiai, Vidùklė and others) pronounce mnsà/me.nsà/mensà (used in literature by D.Poška, S.Stanevičius and others). The word (in literary language it would look like męsa) is common with Old Prussian mensā „mėsa“, Lettish mìesa „kūnas“, the Old Slav. męso. This is supported by the phonetics and geography of the word (the mensa areal as if extends the Old Prussian –Skalviai mensā). 2. The form meisa (Kuršė́nai, Raudė́nai, Ùžventis and others) is supposed to have stemmed from mensa due to polarization, the same as áižuolas, áržuolas, áužuolas ← ánžuolas („ąžuolas" in literary language), žem. ọ̃ršọs ← ọ̃nšọs<vanšas („vą̃šas" in literary language), bruišė/bruñšė „kuoja, rauda". 3. The word pronounced as me·sa (used in the so-called fishers dialect in Prussia and at present in the Aukštaičiai dialects round Smaliniñkai) must have appeared in the following way: mensa → meisa (due to polarization) > me·sa (Northern Žemaičiai and Southern Žemaičiai Švė́kšna and Gar̃damas dialects); mensa> me·sa (Western Žemaičiai and the above-mentioned Aukštaičiai dialects).